2017
DOI: 10.1088/1361-648x/aa693e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the work function of stepped metal surfaces by adsorption of organic molecules

Abstract: Understanding the binding mechanisms for aromatic molecules on transition-metal surfaces, especially with defects such as vacancies, steps and kinks, is a major challenge in designing functional interfaces for organic devices. One important parameter in the performance of organic/inorganic devices is the barrier of charge carrier injection. In the case of a metallic electrode, tuning the electronic interface potential or the work function for electronic level alignment is crucial. Here, we use density-function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…In fact, the π-conjugated aromatic molecules, particularly benzene (BZ), and even mono- and polysubstituted aromatic oxygenates of phenolics (e.g., phenol, anisole, and guaiacol) or halogenated BZ have been employed to study the important role of aromaticity and van der Waals (vdW) interactions in the binding mechanism on metal surfaces including weakly bound systems (e.g., Cu, Ag, and Au) and strongly bound systems (e.g., Rh, Pd, Ir, and Pt); however, their binding strengths calculated using generalized gradient approximation (GGA)-type functionals were severely underestimated with respect to the experimentally measured values. This leads to the employment of nonlocal vdW correlation functionals ,, (e.g., Perdew–Burke–Ernzerhof (PBE) + vdW surf , optB88-vdW, optB86b-vdW, vdWDF, vdW-DF2, BEEF-vdW, and PBE-dDsC) or other schemes (e.g., random phase approximation) for describing the contributions of vdW-dispersion interactions in chemisorbed systems.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the π-conjugated aromatic molecules, particularly benzene (BZ), and even mono- and polysubstituted aromatic oxygenates of phenolics (e.g., phenol, anisole, and guaiacol) or halogenated BZ have been employed to study the important role of aromaticity and van der Waals (vdW) interactions in the binding mechanism on metal surfaces including weakly bound systems (e.g., Cu, Ag, and Au) and strongly bound systems (e.g., Rh, Pd, Ir, and Pt); however, their binding strengths calculated using generalized gradient approximation (GGA)-type functionals were severely underestimated with respect to the experimentally measured values. This leads to the employment of nonlocal vdW correlation functionals ,, (e.g., Perdew–Burke–Ernzerhof (PBE) + vdW surf , optB88-vdW, optB86b-vdW, vdWDF, vdW-DF2, BEEF-vdW, and PBE-dDsC) or other schemes (e.g., random phase approximation) for describing the contributions of vdW-dispersion interactions in chemisorbed systems.…”
Section: Introductionmentioning
confidence: 99%
“…The work function of a metal surface [1], the work required at temperature T = 0 K to move an electron from the metal to infinity, is relevant for, e.g.,the behavior of electronic devices [2], the energetics of molecules at surfaces [3], including reactions [45], and electronic states confined near surfaces [6]. Practical surfaces are finite in size and contain plenty of inhomogeneities that cause local variations of the electrostatic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al investigated the benzene adsorption on stepped Ag(211), (533), (322), (755), and (544) surfaces. They found that the work function change of the surface was strongly related to the density of the steps [23]. In addition, the adsorption energy of benzene on the Ag(322) surface was found to be the strongest among all the considered systems, which was 9% stronger than that on Ag(111).…”
Section: Introductionmentioning
confidence: 98%
“…In this study, the ORR mechanism of the Ag(322) surface was investigated using the SCAN-rVV10 method. The Ag(322) surface was selected since it is a stable stepped surface with high reactivity [23,40], which can be reflective of the features of nanoparticles. The results showed that the dissociative pathway was energetically preferred for ORR on Ag(322).…”
Section: Introductionmentioning
confidence: 99%